Ok, i have go to a point working through a question where i am having to show that the LHS = RHS but cant seem to.... is the following possible or have i gone wrong somewhere earlier in my calculations?
If P(Ak) = a + b*
Then use the equivalent formula for P(Ak+1) and P(Ak-1) and show that....
P(Ak+1) =
Iv uploaded the relevant document for the question. Sorry, i probably didnt include all relevent information of the part i was asking.... i have however managed to do that proof, part (iii), but i am now stuck on part (iv)!
Iv got those boundary conditions A0 = 1 and AN = 1, but im not compeltely sure how to set up the proof.... once iv got it set up, the algebra part should be ok....